2006
DOI: 10.1111/j.1365-2249.2006.03197.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of serotonin on the differentiation of human monocytes into dendritic cells

Abstract: SummaryThe local cytokine environment and presence of stimulatory signals determine whether monocytes acquire dendritic cell (DC) or macrophage characteristics and functions. Because enhanced platelet activation is reported in patients with many allergic disorders, such as atopic dermatitis, plateletderived factors may influence monocytic differentiation into DC. In this study we examined the effect of serotonin, a prototypic mediator of allergic inflammation released mainly by activated platelets at the infla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
49
0
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(51 citation statements)
references
References 44 publications
1
49
0
1
Order By: Relevance
“…Alternatively, the presence of serum factors could modulate or synergize with 5HT, and it might have caused an overestimation of the 5HT influence. In an effort to avoid these potentially confounding issues, we have carried out all experiments on macrophages maintained in serum-free medium for 48 h. Thus, apart from the cell type-specific nature of 5HT actions, the distinct medium used for assaying 5HT might explain the discrepancy between the lack of effect of 5HT on IL-10 release seen in our experiments and those of others (20,49) and the positive action of 5HT in IL-10 production described in human alveolar cells and monocytederived dendritic cells (22,23). Despite these discrepancies, our results are in agreement with the lack of effect of 5HT 2 agonists on the LPS-induced monocyte cytokine production (21).…”
Section: Discussionmentioning
confidence: 42%
See 1 more Smart Citation
“…Alternatively, the presence of serum factors could modulate or synergize with 5HT, and it might have caused an overestimation of the 5HT influence. In an effort to avoid these potentially confounding issues, we have carried out all experiments on macrophages maintained in serum-free medium for 48 h. Thus, apart from the cell type-specific nature of 5HT actions, the distinct medium used for assaying 5HT might explain the discrepancy between the lack of effect of 5HT on IL-10 release seen in our experiments and those of others (20,49) and the positive action of 5HT in IL-10 production described in human alveolar cells and monocytederived dendritic cells (22,23). Despite these discrepancies, our results are in agreement with the lack of effect of 5HT 2 agonists on the LPS-induced monocyte cytokine production (21).…”
Section: Discussionmentioning
confidence: 42%
“…In human alveolar macrophages, serotonin inhibits IL-12 and TNF-a release, but it increases IL-10, NO, and PGE 2 production via 5HT 2 receptors (22). In the case of dendritic cells, 5HT impairs GM-CSF/IL-4-driven human monocyte-derived dendritic cell (MDDC) differentiation by reducing costimulatory molecule and CD1a expression as well as MLR stimulatory activity while increasing CD14 levels (23) and IL-10 production through 5HT 1 or 5HT 7 receptors (23). Others have shown that 5HT is shuttled from dendritic cells to naive T lymphocytes as a means to modulate T cell activation, proliferation, and differentiation (24), and that it might be necessary for optimal macrophage accessory function (25).…”
mentioning
confidence: 99%
“…recently that serotonin specifically modulates macrophage polarization by promoting acquisition of an anti-inflammatory state, which is characterized by inhibition of LPS-induced release of IL-12 and TNF-a by M-CSF-treated (M2) macrophages and downregulation of genes associated with an M1 phenotype (including MMP12 and CCR2) (36,37). The differential expression of 5HT2B and 5HT7 serotonin receptors on M2 and M1 macrophages may be important for determining the effects of serotonin in monocyte subsets (37). It would be interesting to assess further the contribution of platelet serotonin to the effects of activated platelets that we observed in this study.…”
Section: Discussionmentioning
confidence: 99%
“…It is conceivable that allergen exposure triggers the release of 5-HT from immature skin DCs. Signaling by 5-HT 7 receptors drives the maturation of IL-8-and IL-10-producing DCs [61,62] and can potentiate allergic responses by promoting the activation of Th2 cells. Thus, regulation of microenvironmental 5-HT, as well as potentially other biogenic amines, might be important for the maintenance of resting DCs in peripheral tissues.…”
Section: Role Of Neurotransmitters In Immune-related Diseasesmentioning
confidence: 99%